Exploring Strategies for Vocabulary Learning and Teaching for ESL Learners–A Literature Review (Sains Humanika, 2013)
There is much interest about how ESL vocabulary should be taught to learners, particularly at the elementary level in an attempt to give learners a good foundation of the target language and to enable them to deal with spoken and written texts with confidence. In this paper we discuss the issues surrounding vocabulary learning and teaching, namely, context, number of repetitions, type of words chosen, number of words chosen and level of processing. We then build upon that discussion to provide a literature review of the strategies adopted for the teaching of ESL vocabulary and which have been found to produce favourable results in the contexts they were applied. Implicit learning and explicit teaching notions are examined and incidental and intentional vocabulary learning strategies are explored as probable options that could be supported to suit individual needs.
Keywords: Implicit learning; explicit teaching; vocabulary learning strategy